2016
DOI: 10.1177/0706743715621255
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Fidelity to Suicide Reporting Guidelines in Canadian News Media: The Death of Robin Williams

Abstract: Objective: Mindset is a short recently-published booklet funded by the Mental Health Commission of Canada outlining evidence-based guidelines and best practices for journalists writing about mental health and suicide. Our study aimed to assess fidelity to Mindset recommendations in Canadian newspaper reports of a recent celebrity suicide. A secondary aim is to identify common themes discussed in these newspaper articles. Methods: Articles about Robin Williams' suicide from major Canadian newspapers were gather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 12 publications
9
49
2
1
Order By: Relevance
“…Our findings on using direct wording (63.9%), providing detailed information (74.5%), and reporting the contents of the suicide note (44.6%) were very similar to those of Kim’s [ 27 ] study, where percentage of these items were 64, 75 and 45%, respectively. The overall percentage of articles speculating or jumping to conclusions (36.7%) was similar to the results of Creed and Whitley (34.8%) [ 23 ] and Utterson et al’s (30.1%) [ 26 ] studies. Similarly, the results for providing hotline information (1.4%) and educating the public (2.2%) aligned with the studies by Ramadas and Kuttichira [ 24 ] and Harshe et al [ 25 ], who found nearly zero cases for these guideline items.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings on using direct wording (63.9%), providing detailed information (74.5%), and reporting the contents of the suicide note (44.6%) were very similar to those of Kim’s [ 27 ] study, where percentage of these items were 64, 75 and 45%, respectively. The overall percentage of articles speculating or jumping to conclusions (36.7%) was similar to the results of Creed and Whitley (34.8%) [ 23 ] and Utterson et al’s (30.1%) [ 26 ] studies. Similarly, the results for providing hotline information (1.4%) and educating the public (2.2%) aligned with the studies by Ramadas and Kuttichira [ 24 ] and Harshe et al [ 25 ], who found nearly zero cases for these guideline items.…”
Section: Discussionsupporting
confidence: 82%
“…The levels of concordance and discordance of media reports with suicide guidelines can provide important implications for further research and the improvement of the current guidelines. Creed and Whitley [ 23 ] found that 55% of the Canadian newspapers that reported on the suicide of a famous figure had adhered to Mindset’s guidelines by up to 80%. In the study of Ramadas and Kuttichira [ 24 ], they referred to the WHO guidelines and the suggestions of professionals in the related field to create their analytical framework.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study examining adherence to Mindset's 14 specific recommendations in the aftermath of a celebrity suicide found that most recommendations were followed (range of adherence was 65% to 99% of articles), except for the recommendation to tell people considering suicide how they can get help (present in only 27% of articles). 48 The original CPA position paper on media reporting and suicide 1 garnered controversy from some who expressed scepticism about the evidence base for suicide contagion, 49 and argued that perceived efforts to suppress suicide-related stories are counter-productive. 50 In the interim, there has been increased engagement between mental health professionals and the media via informal dialogue surrounding specific reports, through symposia at the CPA annual meeting, and during and after Canada's first media forum for suicide prevention, held in Toronto in November, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Les études canadiennes qui examinent la couverture médiatiqueen général et selon les lignes directrices ci-dessus-sont limitées. Une étude récente examinant l'observance des 14 recommandations spécifiques de Mindset à la suite du suicide d'une célébrité a constaté que la plupart des recommandations ont été respectées (l'échelle de l'observance allait de 65 % à 99 % des articles), excepté en ce qui concerne la recommandation de dire aux gens qui envisagent le suicide comment ils peuvent obtenir de l'aide (présente dans seulement 27 % des articles) 48 .…”
Section: Introductionunclassified
“…The guidelines also recommend including information on the role of treatable mental illness, where and how to seek help for suicidal thoughts, and a message of hope that suicide is preventable. But specific information on individual deaths by suicide continues to be published; the suicide of the actor Robin Williams is an example of the guidelines not being fully followed 1718…”
Section: Introductionmentioning
confidence: 99%